Juvenile justice reform and restorative justice building theory and policy from practice - Bazemore, S. Gordon; Schiff, Mara; Gale Group (Cullompton, U.K. Willan Publishing, 2005)
Provides an overview of the restorative justice conferencing programs currently in operation in the United States, paying particular attention to the qualitative dimensions of this, based on interviews, focus groups and ethnographic observation.
Restorative justice, restorative group conferencing, and juvenile justice -- Principles to practice: intermediate outcomes, intervention theories, and conferencing tasks -- Prevalence and scope of restorative decision-making: findings from a national inventory and survey on restorative conferencing for youth -- Methodology for the qualitative study and description of conference stages and phases -- Repairing harm in the conferencing environment -- Stakeholder involvement in the conferencing environment -- Community/government relationship and role transformation -- Looking back and moving forward: conclusions, implications, and an agenda for future research.
Keywords: Juvenile justice, Administration of -- United States; Restorative justice -- United States; Juvenile corrections -- United States; Community-based corrections -- United States; Electronic books